2014
DOI: 10.1007/s10753-014-9813-5
|View full text |Cite
|
Sign up to set email alerts
|

Aging Reduces the Expression of Lung CINC and MCP-1 mRNA in a P. aeruginosa Rat Model of Infection

Abstract: We investigated dynamic changes of inflammatory cell infiltration and expression of cytokine-induced neutrophil chemoattractant (CINC) and monocyte chemoattractant protein-1 (MCP-1) mRNA in aged rats with Pseudomonas aeruginosa pulmonary infection. Disease manifestation and lung tissue pathology (lesion dispersion, inflammatory reactions, tissue edema and bleeding) were more severe in aged rats than young rats. At various time points, lung tissue polymorphonuclear neutrophil and mononuclear macrophage numbers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Neutrophil migration into the lung was also shown to be impaired in aged mice and rats (e.g. aged 18–24 months) following infectious challenges such as Francisella tularenesis , Pseudomonas aeruginosa, influenza A (Mares, et al 2010; Wen, et al 2014; Chen, et al 2014; Birmingham, et al 2014). This impairment might be attributed to a delay in the kinetics of neutrophil responses.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil migration into the lung was also shown to be impaired in aged mice and rats (e.g. aged 18–24 months) following infectious challenges such as Francisella tularenesis , Pseudomonas aeruginosa, influenza A (Mares, et al 2010; Wen, et al 2014; Chen, et al 2014; Birmingham, et al 2014). This impairment might be attributed to a delay in the kinetics of neutrophil responses.…”
Section: Discussionmentioning
confidence: 99%
“…studies reported lower expression of inflammatory mediators and higher levels of antioxidants in infants/juveniles 44,58 and a more activated inflammatory milieu in the middle aged/elderly 73,75,82,83,85,88 when compared with adults. Data on the number of resident alveolar macrophages and neutrophils were conflicting.…”
Section: Critical Care Medicinementioning
confidence: 98%
“…40,65,68,75,77,80,82,83 Given that each model produces different lung injury modifying the molecular mechanisms activated, 29 we present results on the pulmonary response to injury stratified by type of pulmonary insult (tables 4 and 5). 73,78,82,83,88 In addition, macrophage function in the pneumonia models was impaired in these age groups and associated with a decreased clearance of bacteria (tables 4 and 5). Independent of the model used, in most studies, the recruitment of neutrophils into the lung was lower in infants/juveniles 44,46,51,52,54,[56][57][58]60,61 (table 4) and higher in the middle aged/elderly 40,[65][66][67]69,[72][73][74][76][77][78][79][80][81]86,87,89 (table 5), compared with adults.…”
Section: Critical Care Medicinementioning
confidence: 98%
See 2 more Smart Citations